Investigating the management information needs of academic Heads of Department: a Critical Success Factors approach - Francis Green; Brendan Loughridge (Information Research: An International Electronic Journal)
This paper describes a research project in the Department of Information Studies at the University of Sheffield. With funding from the British Library Research and Development Department a critical success factors-based investigation of the management information needs of academic Heads of Department in an number of English universities was undertaken in 1994/1995, following publication of the results of a pilot study byPellow and Wilson (1993). Senior academic staff, university administrators and librarians in sixteen universities were interviewed between December, 1994 and March, 1995. Collation of data and analysis of results have been completed